Problematika Profesi Advokat Dalam Beracara di Lingkungan Pengadilan Agama - Andri Nurwandi (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to determine the problem of the advocate professional problem in Religious Courts in Kota Kisaran. This study uses a qualitative approach. Data is collected using interview methods. The interviewee are advocates, clients and implementers of religious courts. The sample used is snowball sampling. It can be concluded that problem faced by advocates from their clients during the proceedings in the religious court includes; there are so many clients who are dishonest in giving information that is conveyed to lawyers has hampered process of proceedings before the court, the inconsistency of honorarium agreed in the initial agreement. Due to the absence of maximum or minimum advocate fees in the prevailing laws and regulations, lack of trust the community towards advocates, and the client's paradigm that is wrong to advocates who think that the problem delegated by the client to the attorney is believed will get the results as he wishes, namely the case will always be won, not to get the right solution that will get the benefit and get the verdict as fair as possible.